There's Still Work to Be Done. Issue 5 (24th November 2022) - Lyerly, Eric
Abstract : I'm extremely excited to be the new editor of Disability Compliance in Higher Education. Joan Hope, Ph.D. was a great friend and mentor to me and many others at Wiley. Her writing and editorial talents will be sorely missed in our higher education newsletter group. I'm eager to take up the baton and continue the legacy of this terrific publication. I hope we can continue to play a small part in helping the profession grow and move forward.